National language comprehension in rural Sabah - Kroeger, Paul R. (Journal of Modern Languages, 2017)
From 1978 to 1981, the Summer Institute of Linguistics carried out a linguistic survey of the state of Sabah, East Malaysia, in cooperation with the state government. The survey, described in King and King (1985), was carried out in two phases. The first phase focused on gathering lexical information, in the form of wordlists; the second phase involved direct testing of intelligibility between related dialects and languages.